Nilai-Nilai Budaya Melayu Riau pada Kebijakan Mitigasi Perubahan Iklim - Zulkifli, Afni; Sari, Fara Merian; Prihati, Prihati; Rianita, Dian (International Journal of Demos (IJD), 2022)
AbstractThe serious global problem facing mankind today is climate change which requires adaptation and mitigation efforts. The purpose of this study was to determine the values contained in the Riau Malay Teaching Guide in relation to climate change mitigation policies. This study uses a qualitative method with an analytical approach to popular culture documents recorded by Tenas Effendy, Tunjuk Ajar Melayu (TAM) which has been designated as an intangible cultural heritage (WBTB) of Indonesia, with other main data sources observation and interviews with relevant sources. The writing uses a post-critical ethnographic approach, which has the principle of elevating the emic perspective of local culture in the midst of ethical goals and perspectives, namely climate change mitigation policies. Found various values in TAM that are relevant to the implementation of climate change mitigation policies, especially in forest and land fire control activities; the value of local wisdom in Malay teaching and learning is very universal; and there are obstacles because TAM is not a binding formal policy. This research contributes to anthropology in relation to administrative science. Especially finding the novelty of the role of local wisdom in the process and implementation of public policies for climate change mitigation.Keywords:Â  Riau Malay Culture, Tunjuk Ajar Melayu, Climate Change PolicyÂ AbstrakPerubahan iklim menjadi permasalahan global yang serius dihadapi umat manusia yang memerlukan upaya adaptasi dan mitigasi. Kajian ini guna mengetahui kandungan nilai dalam Tunjuk Ajar Melayu Riau dalam kaitannya dengan kebijakan mitigasi perubahan iklim. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis dokumen budaya popular catatan Tenas Effendy, yakni Tunjuk Ajar Melayu (TAM) yang telah ditetapkan ditetapkan sebagai warisan budaya tak benda (WBTB) Indonesia, dengan sumber data utama lainnya observasi dan wawancara dengan narasumber yang relevan. Adapun penulisan menggunakan pendekatan etnografi post kritis dalam hal ini kajian terhadap kebijakan mitigasi perubahan iklim. Ditemukan berbagai nilai-nilai dalam TAM yang relevan dengan implementasi kebijakan mitigasi perubahan iklim khususnya pada kegiatan pengendalian kebakaran hutan dan lahan; nilai kearifan lokal dalam tunjuk ajar Melayu bersifat sangat universal; dan terdapat hambatan karena TAM bukan kebijakan formal yang mengikat. Penelitian ini berkontribusi terhadap antropologi dalam kaitannya dengan ilmu administrasi. Terutama menemukan kebaruan peran kearifan lokal pada proses dan implementasi kebijakan publik untuk mitigasi perubahan iklim.Kata Kunci: Budaya Melayu Riau, Tunjuk Ajar Melayu, Kebijakan Perubahan Iklim